RESEARCH OF TIME STANDARD DEFINITION METHODS OF AIRCRAFT FASTENERS REPLACEMENT - A. S. Solov’ev (Научный вестник МГТУ ГА)
The study of the methods revealed their advantages and disadvantages for further synthesis and optimization. The main task was to improve the most suitable method, which will have the maximum number of affecting factors. The experimental method is highly accurate, but it requires high costs to work on analogues for each specific type of fasteners. The calculated method based on a single experiment allows to determine time standards for various fasteners. The given method does not require high costs for experiments, but like the experimental method, does not take into account performance degradation with continuous operation time. This leads to serious errors in obtaining time standards for a large number of fasteners. The article shows the optimized model of calculated method, based on a linear approximation of dependence of the number of fasteners replacements (removals/installations) on time at multiple intervals. The optimized model allows to obtain time standards of typical fasteners replacement with different geometric characteristic taking into account performance degradation over time. Several experiments on the aircraft were conducted for testing the improved calculated method. On the basis of the experimental data the researchers built graphs of the number of fasteners replacements (removal/installation) on time with different geometric characteristics taking into account performance degradation over time. The data obtained is advisable to use for calculation maintainability factors on aircraft design stages. Program realization of these methods and systematization of the received time standards allow to improve maintainability, due optimization number and position of airframe fasteners and systems units and aviation equipment for the aircraft being designed and modernized. Application of the automated systems of design and analysis will contribute to labor input decrease at the aircraft maintainability analysis.